Numerical study of the bolt-grout interface for fully grouted rockbolt under different confining conditions. (July 2019) - Ho, D.-A.; Bost, M.; Rajot, J.-P.
Abstract: This paper presents a numerical approach to study the bolt-grout interface of fully grouted rockbolts. Two series of pull-out tests of short-length rockbolts under different confining conditions (constant confining pressure, constant confining rigidity) were numerically reproduced, thereby evaluating the influence of confining condition on the bolt-grout interface behavior and its failure mechanisms. For this purpose, emphasis had been placed on three important issues of the numerical models: (1) mechanical imbrication between bolt and grout imposed by bolt ribs, (2) nature of contact between bolt steel and grout: firstly bonded, then de-bonded and (3) constitutive model of grouting material, taking into considering size effects by plastic localization and failure, both in compression and in tension. The comparison between the numerical and the experimental results showed a good agreement between them and allowed us to validate the proposed numerical method investigation for the bolt-grout interface. The numerical results confirm that under high confining pressure, the failure at the bolt-grout interface occurs by shearing, whereas under low confining pressure by crack opening through grout due to dilatancy. The quantitative analysis of the stress and displacement states demonstrated that the bolt-grout interface can be described by a damageable cohesive behavior with friction. This study will be used to develop a generalized constitutive model for the bolt-grout interface, that will be implemented to simulate in-situ long fully grouted rockbolts.